The Economics of University Dropouts and Delayed Graduation: A Survey - Carmen Aina; Eliana Baici; Giorgia Casalone; Francesco Pastore (Institute of Labor Economics (IZA), 2018)
This survey organizes and discusses the theoretical and empirical literature on the determinants of university student achievements. According to the theoretical framework, the decision to invest in tertiary education is a sequential process made under gradually decreasing levels of uncertainty on education costs and future returns. Students, applying a learning by doing approach, update their information set each academic year and revise benefits and costs associated to tertiary education. Accordingly, they decide whether to continue university studies in order to get a degree or to withdraw. This university decisional process is discussed by clustering the determinants of university outcomes into four main categories - students' characteristics, abilities and behavior; parental background and family networks; characteristics of the tertiary education system and its institutions; labor market performance - which are drawn from the empirical evidence. The policy advice resulting from the encompassing analysis is to provide an all-inclusive orientation activity for students, before they enroll at university. A complete understanding of the potential costs and benefits of this human capital investment can in fact reduce the risk of early withdrawal or delayed graduation.
Keywords: H52; I21; I22; I23; J13; J24; 330; university dropout; time-to-degree; tertiary education; human capital theory